1994
DOI: 10.1177/107319119400100303
|View full text |Cite
|
Sign up to set email alerts
|

Acculturation and Performance of Hispanics on Selected Halstead-Reitan Neuropsychological Tests

Abstract: This study investigated the effect of acculturation on Halstead-Reitan neuropsychological test performances on nonimpaired Hispanics. The sample consisted of three groups of 50 subjects, representing distinct levels of acculturation: (a) Mexican-American, (b) Anglo-American, and (c) Mexican. A significant effect ( p > .05) for acculturation was found on several measures, including the Tactual Performance Test (TPT; Dominant, Nondominant, and Total), the Seashore Rhythm Test, and the Halstead Category Test. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
37
3

Year Published

1997
1997
2012
2012

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 90 publications
(43 citation statements)
references
References 12 publications
3
37
3
Order By: Relevance
“…However, since previous studies suggest that acculturation is an important factor in effectively interpreting NP assessments of members of minority groups (Ardila, 1998;Arnold et al, 1994;Manly et al, 1998), a measure of acculturation was included in this study in order to aid in the interpretation of the NP and functional assessments. The fact that, unlike previous studies, the current study found no association between NP results and acculturation certainly does not refute previous findings.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, since previous studies suggest that acculturation is an important factor in effectively interpreting NP assessments of members of minority groups (Ardila, 1998;Arnold et al, 1994;Manly et al, 1998), a measure of acculturation was included in this study in order to aid in the interpretation of the NP and functional assessments. The fact that, unlike previous studies, the current study found no association between NP results and acculturation certainly does not refute previous findings.…”
Section: Discussionmentioning
confidence: 99%
“…A key factor in interpretation of NP assessment of a member of any minority group is level of acculturation (Ardila, 1998;Arnold, Montgomery, Castañeda, & Longoria, 1994;Manly et al, 1998). According to Berry (1997), acculturation can be broadly defined as the ability to understand and maneuver within a different, dominant culture from one's own.…”
Section: Methodsmentioning
confidence: 99%
“…Level of acculturation has been shown to affect performance on neuropsychological measures in Hispanic groups (Arnold, Montgomery, Castaneda, & Longoria, 1994). Because no formal measure of acculturation was available in this cohort, we examined the effect of English fluency as an estimate of level of acculturation.…”
mentioning
confidence: 99%
“…Emerging literature points to the signi fi cant impact of numerous sociocultural factors on test performance among ethnic minority individuals, including quality of education [57][58][59] , acculturation [ 37,[60][61][62] , language (including bilingualism) [ 59,[63][64][65][66] , and stereotype threat [ 67 ] . There is also potential test bias related to the lack of support for the cultural equivalence and construct validity of several measures with ethnic minority populations [ 13,68,69 ] .…”
Section: Risk For Misdiagnosismentioning
confidence: 99%
“…Multicultural research has demonstrated that neuropsychological performance among neurologically healthy younger and older adults signi fi cantly differs between ethnic minority and non-Hispanic white groups, even after statistically adjusting for other demographic factors (e.g., age, education, and gender) [37][38][39][40][41][42][43][44] . Further, the poor speci fi city of many neuropsychological tests often results in misdiagnosis of neurocognitive disorders among African Americans and Latinos [ 38 , 45-56 ] .…”
Section: Risk For Misdiagnosismentioning
confidence: 99%